Programa educativo para fortalecer la conciencia ambiental en estudiantes de la Especialidad de Ciencias Naturales Facultad de Ciencias de la Educación y Humanidades Universidad Nacional de la Amazonía Peruana Iquitos 2022 - León Flores, Roxana del Pilar (2025)
Below, we present the most relevant results regarding the research carried out to evaluate the effect of the educational program to strengthen environmental awareness in university students during the year 2022. The evaluative methodology was used, field design, univariate, quasi experimental, longitudinal, with two groups, using the pre-test and post-test to collect data through a Questionnaire.The study unit was made up of 66 students specializing in Natural Sciences, divided into a control and experimental group.The results demonstrate the existence of a significant difference between the entry and exit tests in the group where the experiment was applied.The research concludes that the implementation of the educational program contributes significantly to the development of environmental awareness in students of the Natural Sciences specialty of the Faculty of Educational Sciences and Humanities of the National University of the Peruvian Amazon, Iquitos 2022.